Integrative Epistemology in RPS Development, Teaching Materials, and Learning Methods in Islamic Education - Abdul Wahab; Haris Riadi; Mardiyah Mardiyah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
In the context of Islamic Religious Education (PAI), epistemology not only emphasizes the importance of knowledge as a path toward Allah but also encourages the integration of revelation and reason within the learning process. This article outlines how integrative epistemology can be implemented in the design of Semester Learning Plans (RPS), teaching materials, and PAI instructional methods to produce learning that is meaningful, contextual, and oriented toward the development of Islamic character. This research aims to conceptually examine the implications of integrative epistemology on three essential components of higher education practice: Semester Learning Plans (RPS), Teaching Materials, and Instructional Methods. Integrative epistemology is an effort to unify religious and general sciences within a single, holistic scientific paradigm. As a framework that rejects the dichotomy between religious and secular sciences, it emphasizes the unity of knowledge sources, whether derived from revelation (naqli) or reason and experience (aqli/kauni). Results show that this application demands a paradigm shift in micro-curriculum design, encompassing spiritual dimensions and interdisciplinary approaches like PjBL to produce insan kamil.